Exploring the dimension of internal brand citizenship behavior in Malaysia: A case of northern Malaysia hotel - Hasan, Hasnizam; Md. Salleh, Salniza; Hussin, Zolkafli (World Business Institute, Australia, 2011)
This study attempts to explore the dimension of internal brand citizenship behavior in Malaysia. As there is a dearth of research in understanding employees’ brand behavior and inconsistent terminology used in explaining employees’ brand consistent behavior, the study that attempt to explore the dimension of such behavior considered utmost important especially in facing this challenging business horizon.The random survey of 288 hotels’ employees of three to five star hotels from four major states in the northern region of Malaysia revealed that brand citizenship behavior is best explained by multidimensional concept.The study revealed that, brand citizenship behavior consists of helping behavior, sportsmanship, self-brand-development and brand endorsement. Contribution, limitation and future research also were addressed at the end of the discussion.